COMPARISON OF CYBER SECURITY POLICIES OF TÜRKİYE AND ENGLAND - ÜNVER, Gül Nazik (Cyberpolitik Journal, 2024)
This study evaluates and presents a comparative analysis of all political, strategic, educational, legal, economic, social and organizational aspects of Türkiye and England, which implement cyber security policies. In this study, the analysis of cyber security strategies followed by Türkiye and England has been tried to be revealed. In this study, it is seen that cultural differences play an important role in the cyber field of developed states like England and developing states like Türkiye. Cyber security policies implemented in Türkiye and England adopt a more flexible approach. As a result of this research, it has been seen that these two countries attach importance to their economic and individual dimensions. The study firstly claims that it is possible to analyze cyber security policies in five dimensions comparatively according to the Global Cyber Security Index (GCI) data and that cyber policies interact at an international level. Cyber security policies include important strategic issues related to security. Secondly, it shows how Türkiye and England design and implement their national cyber security policies, how they approach counter-strategies, and how they respond to increasing threats in the cyber space. In this context, thirdly, by comparing these two countries within various cyber security indices, it is discussed how the best cyber policies can be for countries in the cyber field. Finally, suggestions are made to guide future research on this subject.